Phosphoproteomics Reveals Regulation of Secondary Metabolites in Mahonia bealei Exposed to Ultraviolet-B Radiation - Liu, Amin; Liu, Shengzhi; Li, Yaohan; Tao, Minglei; Han, Haote; Zhong, Zhuoheng; Zhu, Wei; Tian, Jingkui (Frontiers in Plant Science, 2022)
Mahonia Bealei (M. Bealei) is a traditional Chinese medicine containing high alkaloid content used to treat various diseases. Generally, only dried root and stem are used as medicines, considering that alkaloid content in M. bealei leaves is lower than in stems and roots. Some previous research found that alkaloid and flavonoid contents in the M. bealei leaves may increase when exposed to ultraviolet B (UV-B) radiation. However, the underlying mechanism of action is still unclear. In this study, we used titanium dioxide (TiO2) material enrichment and mass-based label-free quantitative proteomics techniques to explore the effect and mechanism of M. bealei leaves when exposed to UV-B treatment. Our data suggested that UV-B radiation increased the ATP content, photosynthetic pigment content, and some enzymatic/non-enzymatic indicators in the leaves of M. bealei. Moreover, phosphoproteomics suggested phosphoproteins related to MAPK (mitogen-activated protein kinase) signal transduction and plant hormone brassinosteroid signaling pathway as well as phosphoproteins related to photosynthesis, glycolysis, tricarboxylic acid cycle (TCA cycle), and amino acid synthesis/metabolism pathway were all affected by the UV-B radiation. These results suggested that the UV-B radiation activated the oxidative stress response, MAPK signal transduction pathway, and photosynthetic energy metabolism pathway, which may lead to the accumulation of secondary metabolites in M. bealei leaves.